Cell size modulation by CDC25 and RAS2 genes in Saccharomyces cerevisiae. - Baroni, M D (1989)
A detailed kinetic analysis of the cell cycle of cdc25-1, RAS2Val-19, or cdc25-1/RAS2Val-19 mutants during exponential growth is presented. At the permissive temperature (24 degrees C), cdc25-1 cells show a longer G1/unbudded phase of the cell cycle and have a smaller critical cell size required for budding without changing the growth rate in comparison to an isogenic wild type. The RAS2Val-19 mutation efficiently suppresses the ts growth defect of the cdc25-1 mutant at 36 degrees C and the increase of G1 phase at 24 degrees C. Moreover, it causes a marked increase of the critical cell mass required to enter into a new cell division cycle compared with that of the wild type. Since the critical cell mass is physiologically modulated by nutritional conditions, we have also studied the behavior of these mutants in different media. The increase in cell size caused by the RAS2Val-19 mutation is evident in all tested growth conditions, while the effect of cdc25-1 is apparently more pronounced in rich culture media. CDC25 and RAS2 gene products have been showed to control cell growth by regulating the cyclic AMP metabolic pathway. Experimental evidence reported herein suggests that the modulation of the critical cell size by CDC25 and RAS2 may involve adenylate cyclase.